2018
DOI: 10.1002/mrm.27229
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural network for segmentation of knee joint anatomy

Abstract: The combined CNN, 3D fully connected CRF, and 3D deformable modeling approach was well-suited for performing rapid and accurate comprehensive tissue segmentation of the knee joint. The deep learning-based segmentation method has promising potential applications in musculoskeletal imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
140
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 56 publications
3
140
1
Order By: Relevance
“…7 Deep CNN-based methods have achieved state-of-the-art performance in many medical image segmentation tasks including segmenting brain tumors, 8,9 tissues, 10,11 and multiple sclerosis lesions, 12 cardiac, 13,14 liver, 15 and lung 16 tissues, and musculoskeletal tissues such as bone and cartilage. [17][18][19] On the other hand, medical image segmentation is typically seen as a multiclass labeling problem which is closely related to the supervised semantic segmentation described in most segmentation CNN studies. In particular, convolutional encoder-decoder (CED) networks have proven to be highly efficient in the medical image domain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7 Deep CNN-based methods have achieved state-of-the-art performance in many medical image segmentation tasks including segmenting brain tumors, 8,9 tissues, 10,11 and multiple sclerosis lesions, 12 cardiac, 13,14 liver, 15 and lung 16 tissues, and musculoskeletal tissues such as bone and cartilage. [17][18][19] On the other hand, medical image segmentation is typically seen as a multiclass labeling problem which is closely related to the supervised semantic segmentation described in most segmentation CNN studies. In particular, convolutional encoder-decoder (CED) networks have proven to be highly efficient in the medical image domain.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated the successful use of a fully connected 3D conditional random field to regularize segmentation boundaries at tissue interfaces. 9,11,18 The 3D surface shape-based morphological deformable approach has also proven to be highly efficient to maintain desirable geometrical shape for segmented objects in combination with CNN-based segmentation method. 17,18 Because these postprocessing steps typically require no graphics processing unit F I G U R E 7 Example of bone and cartilage segmentation for a 64year-old male subject with severe knee osteoarthritis performed on the T2-FSE image dataset.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning was used to provide automatic detection of artery regions in the reconstructed images, from which an artery contrast enhancement curve can be obtained to guide the selection of desired contrast phases for clinical use. Specifically, a convolutional encoder‐decoder (CED) network (Supporting Information Figure ), previously shown for accurate and efficient multi‐tissue segmentation, was trained to segment the femoral arteries in the prostate images. The images and segmentation masks used for training were obtained on 7 additional prostate data sets (different from the 22 data used for image reconstruction, with IRB approval for waived written informed consent) acquired with the same protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a few convolutional neural network (CNN) based deep learning models, such as SegNet 10 and UNet, 11 have been applied for automatic cartilage and other tissue segmentation in knee MR images. [12][13][14][15][16] In these deep learning based semantic segmentation models, the UNet 12,14 has shown the state-of-the-art performance for knee cartilage semantic segmentation tasks as it maps the feature from earlier encoder layers to later decoder layers to improve segmentation performance. In Norman et al, 12 2D UNet with long skip connection has been used for semantic segmentation of knee cartilages from 2D slices.…”
mentioning
confidence: 99%